Abundance of P‐Glycoprotein and Other Drug Transporters at the Human Blood‐Brain Barrier in Alzheimer's Disease: A Quantitative Targeted Proteomic Study. Issue 3 (6th October 2020) - Storelli, Flavia; Billington, Sarah; Kumar, Aditya R.; Unadkat, Jashvant D.
Abstract : The human blood‐brain barrier (BBB) transporter P‐gp can efflux amyloid‐β (Aβ) out of the central nervous system (CNS). Aβ is thought to be the causative agent for Alzheimer's disease (AD). Using positron emission tomography imaging, we have shown that BBB P‐gp activity is reduced in AD, as quantified by the in vivo brain distribution of the P‐gp probe [ 11 C]‐verapamil. Therefore, the aim of this study was to determine whether this reduced BBB P‐gp activity in AD was due to decreased P‐gp abundance at the BBB. Using targeted proteomics, we quantified the abundance of P‐gp and other drug transporters in gray matter brain microvessels isolated from 43 subjects with AD and 38 age‐matched controls (AMCs) from regions affected by AD (hippocampus and the parietal lobe of the brain cortex) and not affected by AD (cerebellum). First, P‐gp abundance was decreased in the BBB of the hippocampus vs. the cerebellum in both subjects with AD and AMCs, and therefore was not AD‐related. In addition, gray matter BBB abundance of P‐gp (and of other transporters) in the hippocampus and the parietal lobe was not different between AD and AMC. The gray matter BBB abundance of all drug transporters decreased with age, likely due to age‐dependent decrease in the density of brain microvessels. Collectively, the observed reduced in vivo cerebral BBB P‐gp activity in AD cannot be explained by reduced abundance of P‐gp at the BBB. Nevertheless, the drug transporter abundance at the human gray matter BBB data provided here can be used to predict brain distribution of drugs targeted to treat CNS diseases, including AD.